α-amylase production obtained from Aspergillus niger ATCC 1004 by solid state fermentation using Croton linearifolius residues as substrate (Research, Society and Development, 2021)
The objective of this work was to optimize the production and characterize α-amylase produced by Aspergillus niger through solid state fermentation, using leaf residues of C. linearifolius as substrate. For optimization, the incubation temperature, initial humidity and fermentation time were combined based on Doehlert experimental design. The highest productivity of the enzyme was 122.88 Ug-1, at 33oC, 70% humidity and 14 days of time. In the enzymatic characterization, the enzyme extract presented pH 5.0 and temperature 50oC, and α-amylase was thermostable up to 60oC, maintaining more than 90% of the activity. In evaluation of the effect of salt addition, sodium carbonate, calcium chloride, iron chloride, and cobalt chloride increased the enzymatic activity of α-amylase, while potassium and sodium from their chlorides served as enzyme inhibitors. The Km and Vmax values ​​found were 0.04 mg/mL and 46.95 µmol/min/mL, respectively, indicating that the substrate has affinity for α-amylase. Therefore, the results demonstrate that the residues of C. linearifolius can be used as a substrate for A. niger in the production of enzymatic extracts, such as α-amylase.